The Authority Of The Financial Services Authority (OJK) In Publishing Insurance Regulation In The Perspective Of Insurance Law In Indonesia - Fauzi, Wetria (Jurnal Hukum & Pembangunan, 2017)
Legal basis of the formation of the Financial Services Authority (OJK) is based on the Article 34 of the Law No. 3 of 2004 on Bank Indonesia. The legislation process was then approved and endorsed the Law No. 21 of 2011 on the Financial Services Authority (OJK). Article 6 of the law gives the OJK authority to supervise both for bank and non-bank financial institution, including insurance agencies. Article 5 of the Insurance Law, OJK is given a mandate to make a regulation to expand the scope of the insurance business activities in accordance with the needs of the society. One of the businesses is investment-based insurance. Regulations made by OJK must not be contrary to the Insurance Law itself. One issue is found on the draft of the OJK regulation regarding the permissibility of general insurance conducting investment-based insurance business.